Deficits in Analogical Reasoning in Adolescents with Traumatic Brain Injury - Krawczyk, Daniel C.; Hanten, Gerri; Wilde, Elisabeth A.; Li, Xiaoqi; Schnelle, Kathleen P.; Merkley, Tricia L.; Vasquez, Ana C.; Cook, Lori G.; McClelland, Michelle; Chapman, Sandra B.; Levin, Harvey S. (Frontiers in Human Neuroscience, 2010)
Individuals with traumatic brain injury (TBI) exhibit deficits in executive control, which may impact their reasoning abilities. Analogical reasoning requires working memory and inhibitory abilities. In this study, we tested adolescents with moderate to severe TBI and typically-developing (TD) controls on a set of picture analogy problems. Three factors were varied: complexity (number of relations in the problems), distraction (distractor item present or absent), and animacy (living or non-living items in the problems). We found that TD adolescents performed significantly better overall than TBI adolescents. There was also an age effect present in the TBI group where older participants performed better than younger ones. This age effect was not observed in the TD group. Performance was affected by complexity and distraction. Further, TBI participants exhibited lower performance with distractors present than TD participants. The reasoning deficits exhibited by the TBI participants were correlated with measures of executive function that required working memory updating, attention, and attentional screening. Using MRI-derived measures of cortical thickness, correlations were carried out between task accuracy and cortical thickness. The TD adolescents showed negative correlations between thickness and task accuracy in frontal and temporal regions consistent with cortical maturation in these regions. This study demonstrates that adolescent TBI results in impairments in analogical reasoning ability. Further, TBI youth have difficulty effectively screening out distraction, which may lead to failures in comprehension of the relations among items in visual scenes. Lastly, TBI youth fail to show robust cortical-behavior correlations as observed in TD individuals.